CD44, SHH and SOX2 as novel biomarkers in esophageal cancer patients treated with neoadjuvant chemoradiotherapy. Issue 1 (October 2015) - Honing, Judith; Pavlov, Kirill V.; Mul, Véronique E.M.; Karrenbeld, Arend; Meijer, Coby; Faiz, Zohra; Smit, Justin K.; Hospers, Geke A.P.; Burgerhof, Johannes G.M.; Kruyt, Frank A.E.; Kleibeuker, Jan H.; Plukker, John T.M.
Abstract Background and purpose Neoadjuvant chemoradiotherapy (nCRT) improves survival in esophageal cancer (EC) patients, but the response to treatment is heterogeneous and little is known regarding prognostic and predictive markers in these patients. CD44, SOX2 and SHH have been implicated in resistance to CRT, possibly through an association with a cancer stem cell phenotype. Material and methods 101 EC patients treated with nCRT and surgery were included. Sufficient pre-treatment biopsy material was present in 71 patients, of which 53 patients were non-complete responders on nCRT (nCR). Protein expression was examined using immunohistochemistry (IHC). Prognostic factors were determined using Cox regression analysis for disease free survival (DFS) and cause specific survival (CSS) in the complete cohort, the pre-treatment biopsies group and post-treatment nCR group. Results Low CD44 expression in the nCR group was an independent prognostic factor for both DFS and CSS (DFS HR 2.81, p = 0.002 and CSS HR 3.48, p = 0.002). Absent SOX2 expression in pretreatment biopsies was related to systemic recurrence (p = 0.029) while low SHH in pretreatment biopsies was an independent prognostic factor for a poor DFS (HR 2.27, p = 0.036). No relation between marker expression and response to nCRT was observed. Conclusions Low expression of CD44 and SHH are associated with a poor survival outcome in EC patients treated with nCRT.